Impact of extreme spring temperature and summer precipitation events on flowering phenology in a three-year study of the shores of Lake Issaqueena, South Carolina. Issue 1 (3rd April 2017) - Cope, Michael P.; Mikhailova, Elena A.; Post, Christopher J.; Schlautman, Mark A.; McMillan, Patrick D.; Sharp, Julia L.; Gerard, Patrick D.
ABSTRACT: This study aimed to investigate the effects of extreme weather events on flowering around Lake Issaqueena (SC, USA) using plant-flowering data collected with Global Positioning System (GPS)-enabled cameras on a monthly basis in 2012, 2013, and 2014. Six species were identified that flowered before and after a late spring test date (30 April) in at least one study year. Sign tests of the consistency of positive or negative differences in the percentages of test species flowering before the late spring test date between years indicated that these test species shifted towards earlier flowering in 2012 (extreme high monthly temperature), but that the consistency of these shifts was only significant when comparing 2012 to 2013. Nine species were identified that flowered before and after a late summer test date (31 August) in at least one study year. Sign tests of the consistency of positive or negative differences in the percentages of test species flowering before the late summer test date between years indicate that these test species shifted towards later flowering in 2013 after two consecutive months of extreme high precipitation in July and August. Warmer spring temperatures can advance flowering, and extreme summer precipitation events can delay flowering.